2014
DOI: 10.1002/2014gl060090
|View full text |Cite
|
Sign up to set email alerts
|

Landscape reaction, response, and recovery following the catastrophic 1918 Katla jökulhlaup, southern Iceland

Abstract: One of the largest recorded glacier outburst floods (jökulhlaups) occurred in 1918, generated by the last major subglacial eruption of Katla volcano in southern Iceland. Using digitized historical topographic surveys and field observations from the main proglacial outwash plain (Mýrdalssandur), we document the reaction of Mýrdalssandur to the 1918 event and subsequent response and recovery. Our analysis highlights the longevity of elevated topography, over the recovery period, and the complete reorganization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…Various aspects of jökulhlaups on the Katla volcano, Iceland, are elaborated in 27 research items (e.g. Duller et al, 2014). The most famous glacial lakes in GLOF hazard/risk studies nowadays -Imja Tsho, Tsho Rolpa (both Nepal Himalayas) and Palcacocha (Peruvian Andes) -have received the attention of 17, 9 and 7 research items, respectively (e.g.…”
Section: Citations and Referencesmentioning
confidence: 99%
“…Various aspects of jökulhlaups on the Katla volcano, Iceland, are elaborated in 27 research items (e.g. Duller et al, 2014). The most famous glacial lakes in GLOF hazard/risk studies nowadays -Imja Tsho, Tsho Rolpa (both Nepal Himalayas) and Palcacocha (Peruvian Andes) -have received the attention of 17, 9 and 7 research items, respectively (e.g.…”
Section: Citations and Referencesmentioning
confidence: 99%
“…Various aspects of jokulhlaups on the Katla volcano, Iceland, are elaborated in 27 research items (e.g., Duller et al, 2014). The most famous glacial lakes in GLOF hazard / risk studies nowadays -Imja Tsho, Tsho Rolpa (both 25…”
Section: Iceland (180 Research Items) 20mentioning
confidence: 99%
“…Warburton (1994) has shown that for a relatively small rainstorm flood the braided channel produced during the flood was re-converted to a single channel in one melt season. A long-term analysis of landscape recovery following the very large 1918 Katla outburst flood (Duller et al, 2014) shows that in terms of net change in volume of sediment added or subtracted to the outwash plain the landscape recovered in approximately 120 years. Despite this, the landscape is still recognisably impacted by the 1918 jökulhlaup (Russell et al, 2010) and sedimentary deposits of the flood are still preserved (Duller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the landscape is still recognisably impacted by the 1918 jökulhlaup (Russell et al, 2010) and sedimentary deposits of the flood are still preserved (Duller et al, 2008). This outcome may be because a large portion of the sediment removal was due to removal by groundwater exfiltration rather than erosion of surface deposits (Duller et al, 2014). Of the recent jökulhlaups to have occurred in Iceland, the largest and most spectacular was the November 1996 jökulhlaup on Skeiðarársandur (Russell and Knudsen, 1999;Russell et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation